2015
DOI: 10.3855/jidc.6731
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics in surgical wards: use or misuse? A newly industrialized country’s perspective

Abstract: Introduction: Studies exploring the appropriateness of therapeutic antibiotic use among surgical patients are limited, particularly in developing countries. Therefore, the aim of our study was to determine the appropriateness of antibiotics prescribed in a surgical setting in Malaysia. Methodology: A prospective observational study was conducted in two surgical wards at a tertiary hospital in Malaysia from November 2012-July 2013. Data was collected using a case report form. The appropriateness of antibiotic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 23 publications
1
36
1
1
Order By: Relevance
“…One of the key factors is inappropriate and excessive prescription of antibiotics, including carbapenems, in the health care setting. Studies on inpatient prescription of antibiotics have been performed and published in half of the South and Southeast Asian countries, and excessive and inappropriate prescription of antibiotics in the inpatient setting has been highlighted as a major issue, ranging from between 10% to 50% of all antibiotics prescribed (97,141,(163)(164)(165)(166)(167)(168)(169). It is unlikely that the situation is better in the other countries (Bangladesh, Sri Lanka, Maldives, Bhutan, Afghanistan, Philippines, Myanmar, Laos, Cambodia, and Timor-Leste), where data are not available.…”
Section: Drivers Of Carbapenem-resistant Gram-negative Bacteriamentioning
confidence: 99%
“…One of the key factors is inappropriate and excessive prescription of antibiotics, including carbapenems, in the health care setting. Studies on inpatient prescription of antibiotics have been performed and published in half of the South and Southeast Asian countries, and excessive and inappropriate prescription of antibiotics in the inpatient setting has been highlighted as a major issue, ranging from between 10% to 50% of all antibiotics prescribed (97,141,(163)(164)(165)(166)(167)(168)(169). It is unlikely that the situation is better in the other countries (Bangladesh, Sri Lanka, Maldives, Bhutan, Afghanistan, Philippines, Myanmar, Laos, Cambodia, and Timor-Leste), where data are not available.…”
Section: Drivers Of Carbapenem-resistant Gram-negative Bacteriamentioning
confidence: 99%
“…A major proportion of the antibiotics prescribed within hospitals is for surgical patients [1e3]. Inappropriate antibiotic prescribing in surgery is widely reported, with patients at risk of receiving prolonged durations of antibiotics for prophylactic and therapeutic indications [2,3]. In addition, postoperative infections remain one of the most common and costly hospital-acquired infections, and are associated with significant morbidity and mortality [4e8].…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29] Research investigating antibiotic use is extensive, and recent studies continue to show disappointing rates of prophylactic antibiotic use across various patient populations. 8,[30][31][32][33][34] We found that prophylactic antibiotic errors were common in the acute care general surgery setting. This is disappointing, given that surgical "time outs" before incision were in use at the time of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent error was inappropriate timing, particularly the delayed administration of antibiotics after incision, which has been a common trend in prior studies. [30][31][32] Circumstances surrounding acute surgical care, including communication between surgical staff and anesthesiologists, compliance with checklists, competing care priorities and quick transitions from the ED to the OR may be factors involved in such errors. Barriers to provision of appropriate prophylaxis identified in the literature include a perceived low importance and inconvenience, impaired workflow, and organizational communication.…”
Section: Discussionmentioning
confidence: 99%